Expression of Thymic Stromal Lymphopoietin in Immune-Related Dermatoses - Si-Zhe Li; Xin-Xing Jin; Yin Shan; Hong-Zhong Jin; Ya-Gang Zuo (Hindawi Limited, 2022)
Thymic stromal lymphopoietin (TSLP), long known to be involved in Th2 response, is also implicated in multiple inflammatory dermatoses and cancers. The purpose of this study was to improve our understanding of the expression of TSLP in the skin of those dermatoses. Lesional specimens of representative immune-related dermatoses, including lichen planus (LP), discoid lupus erythematosus (DLE), eczema, bullous pemphigoid (BP), psoriasis vulgaris (PsV), sarcoidosis, and mycosis fungoides (MF), were retrospectively collected and analyzed by immunohistochemistry. Morphologically, TSLP was extensively expressed in the epidermis of each dermatosis, but the expression was weak in specimens of DLE. In a semiquantitative analysis, TSLP was significantly expressed in the epidermis in LP, BP, eczema, PsV, sarcoidosis, and MF. TSLP expression was higher in the stratum spinosum in LP, eczema, BP, PsV, and MF and higher in the stratum basale in sarcoidosis and PsV. Moreover, we found positive TSLP staining in the dermal infiltrating inflammatory cells of BP, PsV, and sarcoidosis. Our observation of TSLP in different inflammatory dermatoses might provide a novel understanding of TSLP in the mechanism of diseases with distinctly different immune response patterns and suggest a potential novel therapeutic target of those diseases.